International Financial Reporting Standards (Fourth Edition) : a Practical Guide - Greuning, Hennie van, 1953- 1953- (The World Bank, 2006)
Now in its fourth edition, and with translations into 13 languages, this publication gives readers a broad and basic understanding of the key issues for each International Financial Reporting Standard. It summarizes each standard, providing a quick reference for managers and executives in the private and public sectors who may not have a strong background in accounting. All of the standards issued by the International Accounting Standards Board (IASB) through 31 May 2006 are included in this book